Investigations of polarization distributions of ellipticity states of laser images of punctuate samples of cancer patients and legal aspects of their labor adaptation - Hetmanseva, Nina; Ushenko, Yuriy; Getmantsev, Alexander; Beaser, L.; Sakhnovskiy, M.; Zhytaryuk, V; Slyotov, M; Chuprovska, Yu; Penteleichuk, N. P (My University, 2020)
This research contains materials of experimental studies of the coordinate structure of the distribution of polarization ellipticity of spectral ("red" 0,632m 1  and "blue" 0,414m 2  ) laser images of punctate samples of healthy (group I), preoperative (group II) patients and postoperative (group III) cancer patients. Two-dimensional distributions of elliptic polarization values of the "red" and "blue" laser images of punctate oncological patients of groups I, II and III are presented and analyzed. Samples of stationary values of the polarization ellipticity of laser images of punctate samples of three groups of oncological patients were studied and the patterns of their coordinate and spatial-frequency construction were established. On this basis, polarization criteria for the differentiation of laser images of patients of groups I, II and III are established. The ranges of changes in the statistical moments of the first and fourth orders of the coordinate distribution of polarization ellipticity (“red”  0,632m 1  and “blue” 0,414m 2  ) laser images were studied, and statistical criteria for the differentiation of laser images of patients A, B and C groups were established. Some legal aspects of labor adaptation revealed by the proposed diagnostic methods in labor and social collectives are considered.
Keywords: polarization ellipticity; punctate samples; coordinate distribution